A Qualitative Approach to the Impact of Familial Discord and Social Environment on the Psychological Well-Being of Young Adults - Don, U.; Enabulele, B. H.; Igudia, E. (NIU Journal of Social Sciences, 2026)
The purpose of this study is to examine at the impact of familial discord and social environment on young people' psychological well-being. A qualitative research design was used, with data obtained via interviews with fifteen (15) respondents. Thematic analysis was used to analyze the data.  Findings indicated that familial discord leads to negative psychological states, with sibling rivalry being the most prominent aspect. Unbridled criticism and blame were found to reduce self-esteem and a sense of security. Experiences of familial discord strain interpersonal relationships but also help individuals handle conflicts better. Familial discord significantly affects academic performance, and those affected often rely on religion and spiritual beliefs for coping. The study concludes that familial discord is associated with emotional distress, decreased self-esteem, strained relationships, and impaired academic performance. Effective coping strategies, such as seeking social support and engaging in problem-focused, emotion-focused, avoidance, cognitive, and religious or spiritual coping mechanisms, are crucial for mitigating these negative effects. Keywords:  Familial discord; psychological well-being; young adults; qualitative research